양극산화법에 의한 니오븀 산화물 나노로드 제조 - 정은혜; 장정호; 정봉용; Jung, Eun-Hye; Chang, Jeong-Ho; Jeong, Bong-Yong (전기화학회지, 2011)
The formation of niobium oxide microcones on niobium substrates was investigated in NaF to the HF electrolytes. This condition builds on the uniqueness of the microstructures niobium oxide. The dimensions and integrity of the bulk microstructures were found to be strongly dependent on potential, temperature, electrolyte composition, and anodization time. The anodic oxide was initially amorphous at all temperatures, but crystalline oxide nucleated during anodization. From XRD patterns of the anodized specimens, the microcones consisted of crystalline $Nb_2O_5$. We demonstrated niobium oxide microcone structures with nanorods. The anodized niobium oxide microcone texture revealed nanorod bundles. The surface of $Nb_2O_5$ microcones is very regular and has a nano-scale. The surface morphologies of the nanorods were examined using FE-SEM. EDS analyses show that the anodically prepared niobium oxide consists of $Nb_2O_5$. The aim of this study is to find the condition of forming the favorable nanorods by anodization method. 본 연구에서는 니오븀 산화물을 비교적 저온에서 단시간 동안의 양극산화법을 통해 제조하였다. 이때, 전해질로는 NaF와 HF를 혼합하여 사용하였으며, 20~120 V의 다양한 전압 조건에 따라 생성되는 니오븀 산화물의 미세구조를 관찰하였다. 일반적으로 니오븀 금속의 양극산화 시 초기에 생성된 니오븀 산화물은 무정형 구조이나 반응이 경과함에 따라 점차 결정형 산화물로 성장하게 된다. 이러한 산화물은 XRD 분석을 통하여 결정형의 $Nb_2O_5$ 임을 확인하였고, FE-SEM 분석결과, 그 표면은 매우 밀집된 형태의 나노로드로 이루어진 마이크로콘 산화물임을 알 수 있었다. 적절한 공정변수로 제조된 니오븀 산화물은 마이크로콘 구조 전체 표면에 걸쳐 동일한 크기를 갖는 나노로드 다발을 형성하고 있으며, 이러한 나노 구조는 또한 넓은 표면적을 기대할 수 있어 염료감응 태양전지나 바이오 소재 등에 대한 다양한 분야에 응용될 수 있을 것으로 기대된다.